Classics in entrepreneurship research: Enduring insights, future promises. (1st March 2016) - Gupta, Vishal K.; Dutta, Dev K.; Guo, Grace; Javadian, Golshan; Jiang, Crystal; Osorio, Arturo E.; Ozkazanc-Pan, Banu
Abstract : Academic inquiry into entrepreneurial phenomena has had a rich history over several decades and continues to evolve. This editorial draws attention to the classics: seminal articles that make profound contributions to the development of an academic field in entrepreneurship studies. We focus on the formative years of entrepreneurship research, specifically the 1970s and 1980s, to identify classics using a key informant approach that surveys members of the journal editorial board. Each nominated classic is introduced and discussed by an editorial board member, with particular focus on research opportunities that may be pursued going forward. Analyzing classics allows for the recognition of substantive advances in entrepreneurship research and provides an opportunity to delve into the academic progress achieved in understanding entrepreneurial phenomena.